Contexts, policy, and plan for digital workforce of provincial offices in Thailand / Rujira Rikharom - Rikharom, Rujira (Faculty of Information Management, 2022)
This research was aimed to study digital contexts, policy, and plan for digital workforce of provincial office in Thailand using Delphi technique. In this research, 12 provincial office personnel were determined as key informants. Data were collected by using online interview form and used for content analysis. Results demonstrated that roles and duties of digital workforce according to the mission had relation with positioning standard and operating under The National Strategy 2018-2037 with 5 platforms. The key suggestions of this article were insufficient digital workforce, inconsistent working with the positioning standard of digital workforce, and insufficient professional of digital workforce. Additionally, government organization accepted digital change as being slower than the private organization, due to budget allocation for digital technology procurement was limited